(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
This article focuses on the construction of opposed masculinities and queer desire through the interaction between period pop songs and other composed cues in “Il sorpasso”, considering how period pop songs place protagonists Bruno (Vittorio Gassman) and Roberto (Jean-Louis Trintignant) in Italy’s popular culture landscape and the score articulates a queer attraction that most accounts of this film do not address. This analysis of the interaction between different approaches to film scoring also adds a syntactical dimension to the application of assimilating and affiliating identifications proposed by Kassabian to understand the role of composed and compiled scores in the reproduction of dominant ideology.